Quantitative, Qualitative and Economic Assessment of Agricultural Land Suitability of Rokh Plains Torbat Heydaryeh for Saffron and Wheat Cultivation - Mahdi Abbaszadeh; Amir Salari; HAMID ROHANI (Zirā̒at va Fanāvarī-i Za̒farān, 2019)
Identifying of optimal use of resources and in line with the production of any land is an important step in achieving sustainable development while preserving the ecological system. The purpose of this study is determination quality, quantity and economic suitability of Torbat Heydaryeh lands (Rokh Plain) in Khorasan Razavi for wheat (Triticum Aestivum) and saffron (Crocus Sativus) cultivation. For this purpose, climate condition and soil properties in the study area compare with requirements of wheat and saffron, so qualitative suitability were determined by using FAO method and GIS according to parametric method of Kalogirou. Quantitative and economic evaluation done according to actual yield in each agricultural unit and gross profit per unit area, respectively. Results showed that in this area despite, climate index and yield potential is high but because of soil properties restriction, qualitative suitability is moderate and this restriction is higher for saffron. The results showed that quantitative suitability class is equal or higher than qualitative suitability especially for saffron. Economics results showed that saffron is higher profitable than wheat but its enlargement restricted because of soil limitation, so that its cultivation isn’t recommended. Perform corrective actions and improvement of soil properties in most units can increase production efficiency.